Pengaruh Brand Image dan Financial Tecnology terhadap Minat Investasi Emas pada Gen Z di Surakarta - Erlita Annastasya Sherly; Umi Hanifah; Ety Meikhati (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Interest in investing in gold among Gen Z continues to increase along with digital technology advancements and increasingly easy access to various investment platforms. However, interest in gold investment is not only influenced by technological convenience, but also by the Brand Image of the investment service provider. This study aims to examine the impact of Brand Image and Financial Technology on interest in investing in Gold among Generation Z in Surakarta. This study uses a quantitative approach involving the distribution of questionnaires to 100 Generation Z respondents in Surakarta selected through a purposive sampling technique. Data were analyzed using IBM SPSS Statistics software version 27 by conducting validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²) tests, t-tests, and F-tests. The findings of this study indicate that Brand Image has a positive and significant influence on interest in investing in Gold, with a calculated t-value reaching 5.772 and a significance value of 0.000.